2012
DOI: 10.1016/j.jamcollsurg.2011.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Interleukin-12-Priming During CD8+ T Cell Activation Dramatically Improves Adoptive T Cell Transfer Antitumor Efficacy in a Lymphodepleted Host

Abstract: Background Clinical application of adoptive T cell therapy (ACT) has been hindered by an inability to generate adequate numbers of non-tolerized, functionally active tumor-specific T cells which can persist in vivo. In order to address this, we evaluated the impact of IL-12 signaling during tumor-specific CD8+ T cell priming in terms of persistence and anti-tumor efficacy using an established B16 melanoma tumor adoptive therapy model. Study Design B6 mice were injected subcutaneously with B16 melanoma tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…To determine whether b -restricted gp10025-33 peptide) (29). We found that adoptive T cell therapy in the WT mice slowed tumor growth, but 100% of the WT mice relapsed and succumbed to the progressive diseases ( Figure 9B).…”
Section: Cd25mentioning
confidence: 98%
“…To determine whether b -restricted gp10025-33 peptide) (29). We found that adoptive T cell therapy in the WT mice slowed tumor growth, but 100% of the WT mice relapsed and succumbed to the progressive diseases ( Figure 9B).…”
Section: Cd25mentioning
confidence: 98%
“…Priming activated T cells with the Th1/Tc1 polarizing cytokine IL-12 (15,16) dramatically improves the persistence and antitumor efficacy of CD8 + T cells after adoptive transfer (1719). As IL-7 and IL-15 are elevated after lymphodepletion (2022), this enhanced persistence may be due to an increase in the expression of IL-2Rβ and/or IL-7Rα induced by IL-12 (7,23).…”
Section: Introductionmentioning
confidence: 99%
“…We initially focused on CD8 + T cells conditioned with IL-12 because these cells expand robustly in a lymphodepleted host without a requirement for exogenous cytokines or vaccination (17). This strategy revealed that activated CD8 + T cells require host IL-7, but not IL-15, for maximal initial expansion in a lymphodepleted host.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In this murine melanoma tumor model, activated tumor-reactive CD8 C T cells are derived from pmel-1 TCR transgenic mice. These pmel-1 CD8 C T cells recognize an H-2D b -restricted peptide from the endogenous gp100 tumor antigen that is expressed on the transplantable mouse B16 tumor cells.…”
mentioning
confidence: 99%
“…Using this model, we have previously shown that IL-12 conditioning of the activated T cells prior to adoptive transfer significantly (10-100 fold) improved their ability to persist and mediate antitumor immunity. 6,7 Importantly, the IL-12-conditioned T cells (Tc1) depended on lymphodepletion for optimal antitumor immunity. 6,7 Therefore, this model represents a powerful system for assessing the role of host IL-7 and IL-15 on activated CD8…”
mentioning
confidence: 99%